Residual, regrowth, and new growth of radiofrequency ablation for benign thyroid nodules of different volumes: two-year follow-up results. (31st December 2022) - Chen, Meng-Hsiang; Lin, Wei-Che; Luo, Sheng-Dean; Chiang, Pi-Ling; Chen, Yueh-Sheng; Chen, Wei-Chih; Lin, An-Ni; Wang, Cheng-Kang; Baek, Jung-Hwan; Chen, Hsiu-Ling
Abstract: Introduction: Radiofrequency ablation (RFA) is recognized as an effective technique for the treatment of benign thyroid nodules (BTNs), although the long-term results are limited. This study aimed to evaluate the residual vital volume increase, regrowth, and new growth over a 2-year period after RFA among different nodule volume groups. Subjects and Methods: This retrospective study evaluated 135 patients with 153 BTNs who underwent ultrasound guided RFA. The BTNs were categorized into small (<10 mL), medium (10–30 mL), and large (>30 mL) according to the initial volume of BTNs prior to ablation. The volume changes of each nodule were analyzed at 1, 3, 6, 12 and 24 months after RFA. New growth was defined as the growth in volume not found in the early follow-up on ultrasonography. Results: The initial ablation ratio of all BTNs was 99.67%. The mean volume reduction ratio (VRR) of BTNs was 85.53% after 2-year follow-up. The small nodule group showed a lower VRR compared to the other two groups at the 1-month follow-up, and there was no difference of VRR at the subsequent follow-ups. The incidence of residual vital volume increase was 4.58%. The overall incidence of regrowth was 3.92% and the mean timing of regrowth was 16.71 months. New growth occurred in 18.95% of patients. No further treatment was required in the majority of cases. Conclusion: RFA achieved a clinically relevant volume reduction in different sizes of single BTNs which persisted for at least 2 years, thereby preventing the need for retreatment.